TWO APPROACHES TO THE POSITIONING OF TRANSLATED TEXTS: A COMPARATIVE STUDY OF ITAMAR EVEN - ZOHARS POLYSYSTEM STUDIES AND GIDEON TOURYS DESCRIPTIVE TRANSLATION STUDIES AND BEYOND - Harry Aveling (Soegijapranata Catholic University, 2004)
This paper provides an analysis of the work of two contemporary scholars of Translation theory, Itamar Even-Zohar and Gideon Toury, both of whom work at the University of Tel Aviv. Their studies draw on Russian Formalism. Even-Zohars Polysystem theory pays attention to the ways in which source texts are received by the target culture and within its literary polysystem. He particularly emphasises the way in which source texts are selected by the target literature, and the way in which translated works adopt specific norms, behaviours, and policies which are part of that receiving system. Gideon Toury also sees the act of translation as fulfilling a function allotted by the receiving community and extends Even-Zohars discussion by a more detailed consideration of the role of norms in the translation process. The paper suggests that Tourys ideas have been more readily accepted by the academic community because of the fit with other dimensions of contemporary thought.